Proliferation of Small Arms and Conflict in the Nigeria’s Niger Delta Region - OGUJI , Chukwuemeka A; OKWUADIMMA, Jude C (Socialscientia: Journal of Social Sciences and Humanities, 2021)
One of the biggest security challenges facing Nigeria today is the proliferation of small arms and light weapons. This development whose explosion started in the Niger Delta in the early 1990s has escalated to engulf the whole nation. It now calls for serious attention from state governments, national and even regional organizations. The trade in small arms and light weapons in Nigeria has fuelled ethnic clashes in the Niger Delta, especially between the Ijaws and their immediate neighbors, the Itsekiri and Urhobos as events have shown. This situation aggravates the security problems in the Niger Delta already engendered by the activities of oil Transnationals operating in the oil-rich region. Given this background, the paper explores the origin of the present oil violence in the Niger Delta and how it has been intensified through the use of weapons that are primarily smuggled from some African countries such as Guinea-Bissau, Gabon and Cameroon. The paper concludes by making some suggestions as policy options for the resolution of the armed conflict in the Nigeria’s Niger Delta, with specific reference to the problems of arms proliferation.